(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
In this work, we study density of active interface states Nir between window layer CdS and absorber layer CdTe of heterojunction solar cell CdS/CdTe. The effect of this density on the parameters of solar cell was also explained. Interface state is the result of lattice mismatch of two materials used. Here, we regard interface states as impurity level. In order to understand the behavior of these cells a theoretical model has been developed for pn heterojunction solar cells in which interface recombination between CdS and CdTe is the dominant mechanism of current transport for these cells. The model explains the large junction ideality factor (n>1) and the increased saturation current density in terms of increased density of active interface states Nir .The interface recombination leads to lower values of the open circuit voltage Voc , short circuit current Isc , and fill factor FF. These results are illustrated by numerical calculation of solar cell parameters CdS/CdTe.